Chromium trisulfide-carbon composite microspheres as well as preparation method and application thereof
By reacting chromate with dopamine hydrochloride to form a spherical complex, heat treatment and vulcanization with the sulfur source, dichromium trisulfide-carbon composite microspheres were prepared, solving the problems of agglomeration and insufficient conductivity of dichromium trisulfide nanoparticles, and achieving a lithium-ion battery electrode material with high specific capacity and cycle stability.
Patent Information
- Application Number
- CN202411903584.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The high surface energy of existing dichromium trisulfide nanoparticles leads to agglomeration and accumulation, reducing their active specific surface area and specific capacity, while poor conductivity and volume expansion effects caused by charging and discharge affect the cycling and rate performance of the electrode material.
Dichromium trisulfide-carbon composite microspheres were prepared by reacting chromate and dopamine hydrochloride in an appropriate proportion to form a spherical complex precursor, and heat treatment and vulcanization with the sulfur source under an inert atmosphere. This method uses carbon spheres to carry dichromium trisulfide nanoparticles to avoid agglomeration and to alleviate volume expansion during charging and discharge through the domain-limiting effect of carbon materials.
The specific capacity and cyclic stability of dichromium trisulfide-carbon composite microspheres are improved, their conductivity and rate performance are enhanced, and the electrochemical performance of lithium-ion batteries is significantly improved.
Smart Images

Figure CN119706938A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of micro-nano composite materials, and more specifically, relates to a chromium trisulfide-carbon composite microsphere and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries, as a new energy storage device, have the advantages of long service life and high energy density, which has aroused great research interest. However, the electrode materials of lithium-ion batteries, especially the negative electrode materials, greatly affect the electrochemical performance of energy storage devices, so finding electrode materials with novel structures is crucial to promote the development of lithium-ion batteries and further improve the performance of lithium-ion batteries.
[0003] Transition metal sulfides such as chromium trisulfide (Cr2S3) have high theoretical specific capacity and can be used as negative electrode materials for lithium-ion batteries for energy storage. However, in practical applications, due to the high surface energy of chromium trisulfide nanoparticles, they are prone to agglomeration or accumulation, resulting in a significant reduction in their available active specific surface area, thus causing a reduction in specific capacity. In addition, the poor conductivity of chromium trisulfide and the volume expansion effect caused by long-term charging and discharging can easily lead to the pulverization of electrode materials, resulting in poor cycle capacity and rate capability. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art and provide a method for preparing chromium trisulfide-carbon composite microspheres.
[0005] The purpose of the present invention is to provide chromium trisulfide-carbon composite microspheres prepared by the preparation method.
[0006] Another object of the present invention is to provide the use of the chromium trisulfide-carbon composite microspheres in the preparation of lithium ion batteries.
[0007] Another object of the present invention is to provide a lithium ion battery.
[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0009] The present invention provides a method for preparing chromium trisulfide-carbon composite microspheres, comprising the following steps:
[0010] S1. mixing the chromate solution and the dopamine hydrochloride solution dropwise for reaction, and post-treating to obtain a complex precursor of dopamine and chromate;
[0011] S3. In an inert atmosphere, the complex precursor and the sulfur source are heat treated and sulfurized at 600 to 800° C., and post-treated to obtain chromium trisulfide-carbon composite microspheres;
[0012] Wherein, the molar ratio of dopamine hydrochloride to chromate is (1-2):1.
[0013] The invention provides a method for preparing chromium trisulfide-carbon composite microspheres. The method utilizes chromate to react with dopamine hydrochloride to form a spherical complex, and uses the spherical complex as a template, adds a sulfur source, and obtains chromium trisulfide-carbon composite microspheres through heat treatment and sulfurization. The preparation principle is as follows: dopamine hydrochloride and chromate form a spherical complex precursor in a suitable ratio, and then a sulfur source is added and heat treated. During the heat treatment, dopamine hydrochloride is thermally cracked to form carbon balls, and the sulfur source is decomposed to release hydrogen sulfide. The hydrogen sulfide reacts with chromate in situ to generate chromium trisulfide Cr2S3, which is loaded on the carbon balls to finally obtain chromium trisulfide-carbon composite microspheres.
[0014] In the chromium trisulfide-carbon composite microspheres of the present invention, the chromium trisulfide nanoparticles are highly dispersed in the carbon network, thus avoiding agglomeration and accumulation, exposing more active sites, and facilitating improving the specific capacity of the composite microspheres; at the same time, due to the confinement effect of the carbon material, the volume expansion effect of the chromium trisulfide nanoparticles during charging and discharging is effectively alleviated, which is conducive to enhancing the cycle stability of the composite microspheres; in addition, the close combination with the conductive carbon material improves the overall conductivity of the composite microspheres, which is conducive to improving the rate performance of the composite microspheres.
[0015] The inventors have found through extensive research that only when the molar ratio of dopamine hydrochloride to chromate is (1-2):1, the prepared material has good specific capacity and cycle stability. If the molar ratio is too large, the size of the material will be too large, resulting in a large distance for ions to diffuse from the outside to the inside, affecting the rate performance. In addition, it will cause the carbon content in the material to be too high, resulting in a decrease in the lithium storage capacity of the entire composite material; while if the molar ratio is too small, a spherical composite material cannot be formed, and the carbon content in the material will be too low, resulting in a decrease in the cycle stability of the entire composite material.
[0016] In the present invention, the chromate solution and the dopamine hydrochloride solution must be mixed drop by drop, because the two substances will directly react upon contact. If they are directly mixed and dissolved, the morphology of the final prepared product will be irregular, affecting the battery performance of the product.
[0017] Preferably, the molar concentration of chromate ions in the chromate solution is 0.01 to 0.5 mol / L.
[0018] More preferably, the molar concentration of chromate ions in the chromate solution is 0.05-0.1 mol / L.
[0019] Preferably, the molar ratio of the sulfur source to the chromate is (5-10): 1. More preferably, the molar ratio of the sulfur source to the chromate is (8-10):1.
[0020] Preferably, the chromate is one or more of ammonium chromate, potassium chromate and sodium chromate.
[0021] Preferably, the sulfur source is one or both of thiourea or thioacetamide.
[0022] Preferably, the heat treatment and vulcanization time is 1 to 4 hours. More preferably, the heat treatment and vulcanization time is 1.5 to 2.5 hours.
[0023] Preferably, the temperature of the heat treatment and sulfurization is 650-700° C. The inventors have found that the material prepared at this heat treatment temperature has better battery cycle stability when used to prepare lithium-ion batteries.
[0024] Preferably, in step S2, the reaction is stirred for 10 to 14 hours.
[0025] Preferably, in step S2, the post-treatment is: centrifuging to obtain a precipitate, washing, and drying.
[0026] Preferably, in step S3, the post-treatment is: cooling, water washing, and drying.
[0027] Furthermore, the drying is vacuum drying at 75-85° C. for 10-14 hours.
[0028] Preferably, the inert atmosphere is one or both of nitrogen and argon.
[0029] In addition, the present invention also protects the chromium trisulfide-carbon composite microspheres prepared by the preparation method.
[0030] Furthermore, the present invention provides the use of the chromium trisulfide-carbon composite microspheres in the preparation of supercapacitors, lithium ion batteries or sodium ion batteries.
[0031] The chromium trisulfide-carbon composite microspheres of the present invention can be used as the negative electrode material of the battery to prepare supercapacitors, lithium-ion batteries or sodium-ion batteries. The inventors have found that the lithium-ion battery prepared using the chromium trisulfide-carbon composite microspheres of the present invention can significantly improve the specific capacity stability during multiple charge and discharge processes.
[0032] Preferably, the lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, and the negative electrode sheet comprises a negative electrode material and a current collector.
[0033] At the same time, the present invention also provides a lithium ion battery, wherein the negative electrode material contains the chromium trisulfide-carbon composite microspheres of the present invention.
[0034] Preferably, the negative electrode material also contains a conductive agent and a binder.
[0035] Preferably, the conductive agent is selected from one or more of carbon nanotubes, carbon black, graphene, and acetylene black; and / or the binder is selected from one or more of polyvinylidene fluoride, carboxymethyl cellulose, polyacrylic acid, and polyimide.
[0036] Preferably, in the negative electrode material of the present invention, the mass percentages of chromium trisulfide-carbon composite microspheres, conductive agent and binder are 65-75%: 10-20%: 10-20%.
[0037] The present invention has the following beneficial effects:
[0038] The invention provides a method for preparing chromium trisulfide-carbon composite microspheres. According to the preparation method, chromium trisulfide nanoparticles in the chromium trisulfide-carbon composite microspheres are highly dispersed in a carbon network, agglomeration and accumulation are avoided, more active sites can be exposed, and the specific capacity of the composite microspheres is improved. Meanwhile, due to the confinement effect of the carbon material, the volume expansion effect of the chromium trisulfide nanoparticles during charge and discharge is effectively alleviated, which is beneficial to enhancing the cycle stability of the composite microspheres. In addition, the tight combination with the conductive carbon material improves the overall conductivity of the composite microspheres, which is beneficial to improving the rate performance of the composite microspheres.
[0039] The invention has the advantages of simple preparation method, low cost, rapid and large-scale synthesis and high product yield, and the prepared chromium trisulfide-carbon composite microspheres have a relatively uniform morphology, and the application of the prepared chromium trisulfide-carbon composite microspheres in the preparation of battery materials can significantly improve the cycle stability of the battery. The chromium trisulfide-carbon composite microspheres prepared by the invention have important application value in the fields of supercapacitors, lithium and sodium ion battery electrode materials, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is the XRD pattern of the chromium trisulfide-carbon composite microspheres prepared in Example 1.
[0041] Figure 2 This is a scanning electron microscope image of the chromium trisulfide-carbon composite microspheres prepared in Example 1.
[0042] Figure 3 This is the XRD pattern of the chromium trisulfide-carbon composite microspheres prepared in Example 2.
[0043] Figure 4 This is a scanning electron microscope image of the chromium trisulfide-carbon composite microspheres prepared in Example 2.
[0044] Figure 5 This is the XRD pattern of the chromium trisulfide material prepared in Comparative Example 1.
[0045] Figure 6 This is a scanning electron microscope image of the chromium trisulfide material prepared in Comparative Example 1.
[0046] Figure 7 This is a scanning electron microscope image of the chromium trisulfide-carbon composite microspheres prepared in Comparative Example 2.
[0047] Figure 8 This is a scanning electron microscope image of the chromium trisulfide-carbon composite material prepared in Comparative Example 4.
[0048] Fig. 9 This is a cycle performance diagram of the chromium trisulfide-carbon composite microspheres prepared in Example 1 at a current density of 0.1 A / g.
[0049] Fig.10 This is a cycle performance diagram of the chromium trisulfide-carbon composite microspheres prepared in Example 2 at a current density of 0.1 A / g.
[0050] Fig.11 This is a cycle performance diagram of the chromium trisulfide-carbon composite microspheres prepared in Comparative Example 1 at a current density of 0.1 A / g.
[0051] Fig.12 This is a cycle performance diagram of the chromium trisulfide-carbon composite microspheres prepared in Comparative Example 2 at a current density of 0.1 A / g.
[0052] Fig.13 This is a cycle performance diagram of the chromium trisulfide-carbon composite microspheres prepared in Comparative Example 3 at a current density of 0.1 A / g.
[0053] Fig.14 This is a cycle performance diagram of the chromium trisulfide-carbon composite material prepared in Comparative Example 4 at a current density of 0.1 A / g. DETAILED DESCRIPTION
[0054] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0055] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0056] Example 1
[0057] S1. Dissolve 2mmol dopamine hydrochloride and 2mmol ammonium chromate in 50mL and 20mL water, respectively, under stirring and completely dissolved to obtain a dopamine hydrochloride solution and an ammonium chromate solution;
[0058] S2. Then, the ammonium chromate solution was added dropwise to the dopamine hydrochloride solution under stirring, and the stirring was continued for 12 hours after the addition, and the precipitate was separated by centrifugation, washed, and vacuum dried at 80 ° C for 12 hours to obtain a complex precursor of dopamine and chromate;
[0059] S3. The complex precursor obtained in S2 is placed in a quartz boat, placed in the middle of a tube furnace, and thiourea is used as a sulfur source and reducing agent. 20 mmol of thiourea is placed in a quartz boat, and placed upstream of the complex precursor. After heat treatment and sulfurization at 650°C for 2 hours under nitrogen, it is naturally cooled. The obtained product is repeatedly washed with water for 3 times, and then vacuum dried at 80°C for 12 hours to obtain the final chromium trisulfide-carbon composite microspheres.
[0060] The product has been tested by X-ray diffraction. The position and intensity of each diffraction peak of chromium trisulfide are consistent with the standard diffraction card of hexagonal chromium trisulfide (JCPDS10-0340). Figure 1 The scanning electron microscope image is shown in Figure 2 ,from Figure 2 It can be seen from Figure a that the chromium trisulfide-carbon composite microspheres are microspheres with relatively uniform morphology; Figure 2 Figure b is a local enlarged view, from which it can be seen that the surface of the microsphere is very rough and distributed with many chromium trisulfide nanoparticles.
[0061] Example 2
[0062] S1. Dissolve 4 mmol of dopamine hydrochloride and 2 mmol of ammonium chromate in 50 mL and 20 mL of water, respectively, under stirring and completely dissolved to obtain a dopamine hydrochloride solution and an ammonium chromate solution;
[0063] S2. Then, the ammonium chromate solution was added dropwise to the dopamine hydrochloride solution under stirring, and the stirring was continued for 12 hours after the addition, and the precipitate was separated by centrifugation, washed, and vacuum dried at 80 ° C for 12 hours to obtain a complex precursor of dopamine and chromate;
[0064] S3. The complex precursor obtained in S2 is placed in a quartz boat, placed in the middle of a tube furnace, and thiourea is used as a sulfur source and reducing agent. 20 mmol of thiourea is placed in a quartz boat, and placed upstream of the complex precursor. After heat treatment and sulfurization at 700°C for 2 hours under nitrogen, it is naturally cooled. The obtained product is repeatedly washed with water for 3 times, and then vacuum dried at 80°C for 12 hours to obtain the final chromium trisulfide-carbon composite microspheres.
[0065] The product has been tested by X-ray diffraction. The position and intensity of each diffraction peak of chromium trisulfide are consistent with the standard diffraction card of hexagonal chromium trisulfide (JCPDS10-0340). Figure 3 The scanning electron microscope image is shown in Figure 4 , showing that the product is still a microsphere with relatively uniform morphology.
[0066] Comparative Example 1
[0067] 2 mmol of ammonium chromate and 20 mmol of thiourea were placed in a quartz boat respectively, placed in the middle and upstream of a tube furnace, heat treated and sulfurized at 650°C in nitrogen for 2 hours, the obtained product was repeatedly washed with water for 3 times, and then vacuum dried to obtain chromium trisulfide material.
[0068] The product has been tested by X-ray diffraction and is consistent with the standard diffraction card (JCPDS 10-0340) of hexagonal chromium trisulfide. Figure 5 The scanning electron microscope image is shown in Figure 6 , showing that the product is irregular particles agglomerated together.
[0069] The difference between this comparative example and Example 1 is that no dopamine hydrochloride is added, and ammonium chromate is directly heat-treated with thiourea.
[0070] Comparative Example 2
[0071] S1. Dissolve 0.5mmol dopamine hydrochloride and 2mmol ammonium chromate in 50mL and 20mL water, respectively, under stirring and completely dissolved to obtain a dopamine hydrochloride solution and an ammonium chromate solution;
[0072] S2. Then, the ammonium chromate solution is added dropwise to the dopamine hydrochloride solution under stirring. After the addition is completed, stirring is continued for 12 hours, and then the precipitate is separated by centrifugation, washed, and vacuum dried at 80° C. for 12 hours to obtain a complex precursor formed by dopamine and chromate.
[0073] S3. The complex precursor obtained in S2 is placed in a quartz boat, placed in the middle of a tube furnace, and thiourea is used as a sulfur source and reducing agent. 20 mmol of thiourea is placed in a quartz boat, and placed upstream of the complex precursor. After heat treatment and sulfurization at 700°C for 2 hours under nitrogen, it is naturally cooled. The obtained product is repeatedly washed with water for 3 times, and then vacuum dried at 80°C for 12 hours to obtain the final chromium trisulfide-carbon composite microspheres.
[0074] The only difference between this comparative example and Example 2 is that the molar ratio of dopamine hydrochloride to ammonium chromate is different. The molar ratio of dopamine hydrochloride to chromate in this comparative example is 0.5:2, while that in Example 2 is 2:1.
[0075] The product has been tested by X-ray diffraction, and the position and intensity of each diffraction peak of chromium trisulfide are consistent with the standard diffraction card (JCPDS10-0340) of hexagonal phase chromium trisulfide. Figure 7 , showing that the product is an aggregate of nanosheets.
[0076] Comparative Example 3
[0077] S1. Dissolve 8 mmol dopamine hydrochloride and 2 mmol ammonium chromate in 50 mL and 20 mL water, respectively, under stirring and completely dissolved to obtain a dopamine hydrochloride solution and an ammonium chromate solution;
[0078] S2. Then, the ammonium chromate solution is added dropwise to the dopamine hydrochloride solution under stirring. After the addition is completed, stirring is continued for 12 hours, and then the precipitate is separated by centrifugation, washed, and vacuum dried at 80° C. for 12 hours to obtain a complex precursor formed by dopamine and chromate.
[0079] S3. The complex precursor obtained in S2 is placed in a quartz boat, placed in the middle of a tube furnace, and thiourea is used as a sulfur source and reducing agent. 20 mmol of thiourea is placed in a quartz boat, and placed upstream of the complex precursor. After heat treatment and sulfurization at 700°C for 2 hours under nitrogen, it is naturally cooled. The obtained product is repeatedly washed with water for 3 times, and then vacuum dried at 80°C for 12 hours to obtain the final chromium trisulfide-carbon composite microspheres.
[0080] The difference between this comparative example and Example 2 is that the molar ratio of dopamine hydrochloride to ammonium chromate is different. The molar ratio of dopamine hydrochloride to chromate in this comparative example is 4:1, while that in Example 2 is 2:1.
[0081] The product was tested by X-ray diffraction. The position and intensity of each diffraction peak of chromium trisulfide were consistent with the standard diffraction card (JCPDS10-0340) of hexagonal chromium trisulfide. Its morphology was relatively uniform microspheres, but the size of the microspheres was relatively large.
[0082] Comparative Example 4
[0083] S1. 2 mmol of ammonium chromate was heat treated at 800°C under nitrogen to obtain chromium trioxide, and the chromium trioxide was dispersed in 20 mL of water to obtain a chromium trioxide suspension;
[0084] S2. 2 mmol of dopamine hydrochloride was dissolved in 50 ml of water, and then the chromium trioxide suspension prepared in S1 was added to the dopamine hydrochloride solution under stirring. After the addition, stirring was continued for 12 hours, and then centrifuged and washed, and vacuum dried at 80 ° C for 12 hours to obtain a polydopamine-coated sample;
[0085] S3. The polydopamine-coated sample prepared in S2 was placed in a quartz boat, placed in the middle of a tubular furnace, and thiourea was used as a sulfur source and reducing agent. 20 mmol of thiourea was taken and placed in the quartz boat, and placed upstream of the precursor. After heat treatment and sulfurization at 650°C for 2 hours under nitrogen, the boat was naturally cooled. The obtained product was repeatedly washed with water for 3 times, and then vacuum dried at 80°C for 12 hours to obtain the final chromium trisulfide-carbon composite material.
[0086] In this comparative example, chromium trioxide is first prepared, and then reacted with dopamine hydrochloride to prepare a simple polydopamine-coated product, which is then subjected to heat treatment and vulcanization to obtain a chromium trisulfide-carbon composite material.
[0087] The product has been tested by X-ray diffraction, and the position and intensity of each diffraction peak of chromium trisulfide are consistent with the standard diffraction card (JCPDS10-0340) of hexagonal phase chromium trisulfide. Figure 8 , showing that the product is irregularly agglomerated particles. This comparative example only uses dopamine hydrochloride as a carbon source for simple coating, and the morphology and size of the final product cannot be controlled. The final prepared material is irregularly agglomerated particles.
[0088] Application Examples
[0089] Experimental materials: chromium trisulfide-carbon composite microspheres prepared in Examples 1-2, chromium trisulfide materials prepared in Comparative Example 1, chromium trisulfide-carbon composite microspheres prepared in Comparative Examples 2-3, and chromium trisulfide-carbon composite materials prepared in Comparative Example 4.
[0090] Experimental methods:
[0091] The materials prepared in Examples 1 to 2 and Comparative Examples 1 to 4 are respectively used as electrode active materials for electrochemical lithium storage, and are fully mixed with acetylene black and N-methylpyrrolidone solutions of polyvinylidene fluoride under stirring to form a uniform slurry, and the slurry is evenly applied to a foam copper foil as a current collector, vacuum dried at 110° C., and then rolled to obtain an electrode; wherein the mass percentage of each component in the electrode is: 70% of the material prepared in the example or the comparative example, 15% of acetylene black, and 15% of polyvinylidene fluoride; a lithium sheet is used as a counter electrode, and a solution of ethylene carbonate and diethylene carbonate in a volume ratio of 1:1 is used as an electrolyte, and the electrolyte also contains 1.0 mol / L LiPF6, the diaphragm is a polypropylene film (Celguard-2400), and a two-electrode test cell is assembled in a glove box filled with argon. The battery is subjected to constant current charge and discharge test on a program-controlled automatic charge and discharge instrument, using the CT2001A charge and discharge tester of Wuhan Blue Electric Company, with a charge and discharge current density of 0.1A / g and a voltage of 0.005~3.00V.
[0092] The constant current charge-discharge cycle performance of the prepared battery is shown in the figure below: Fig. 9 As shown, it can be seen that after 100 charge and discharge cycles at a current density of 0.1 A / g, the capacity of the battery is still as high as 1199 mAh / g, and it shows good cycle stability.
[0093] The chromium trisulfide-carbon composite microspheres prepared in Example 2 were used as electrode active materials to prepare a battery with constant current charge and discharge cycle performance. Fig.10 As shown, after 100 charge and discharge cycles at a current density of 0.1 A / g, the battery capacity is still as high as 958 mAh / g, and exhibits good cycle stability.
[0094] The chromium trisulfide material prepared in Comparative Example 1 was used as the electrode active material to prepare a battery with constant current charge and discharge cycle performance. Fig.11 As shown, after 100 charge and discharge cycles at a current density of 0.1 A / g, the capacity of the battery is only 152 mAh / g, showing obvious capacity decay and poor cycle performance. The difference between Comparative Example 1 and Example 1 is that no dopamine hydrochloride is added, and ammonium chromate is directly heat-treated with thiourea to obtain a chromium trisulfide material. After 100 charge and discharge cycles, the capacity of the battery prepared therefrom decreases by 87.32% compared with Example 1.
[0095] The chromium trisulfide-carbon composite material prepared in Comparative Example 2 was used as the electrode active material to prepare a battery with constant current charge and discharge cycle performance as shown in FIG. Fig.12 As shown, after 100 charge and discharge cycles at a current density of 0.1A / g, the capacity of the battery is only 629mAh / g, showing poor cycle stability. The only difference between Comparative Example 2 and Example 2 is that the molar ratio of dopamine hydrochloride to ammonium chromate is different. The molar ratio of dopamine hydrochloride to chromate in this comparative example is 0.5:2, while that in Example 2 is 2:1. After 100 charge and discharge cycles, the capacity of the battery prepared by the comparative example decreases by 34.34% compared with that in Example 2.
[0096] The chromium trisulfide-carbon composite microspheres prepared in Comparative Example 3 were used as the electrode active material to prepare a battery with constant current charge and discharge cycle performance as shown in FIG. Fig.13 As shown, after 100 charge and discharge cycles at a current density of 0.1A / g, the cycle stability is good, but the battery capacity is only 417mAh / g. The only difference between Comparative Example 3 and Example 2 is that the molar ratio of dopamine hydrochloride and ammonium chromate is different. The molar ratio of dopamine hydrochloride to chromate in this comparative example is 4:1, while that in Example 2 is 2:1. After 100 charge and discharge cycles, the capacity of the battery prepared by the comparative example is reduced by 56.47% compared with that in Example 2. The composite microspheres prepared in Comparative Example 3 are large in size, resulting in a large distance for ions to diffuse from the outside to the inside, affecting the rate performance, and the carbon content in the material is too high, resulting in a decrease in the lithium storage capacity of the entire composite material. Although the cycle stability is good, the battery capacity is low.
[0097] The chromium trisulfide-carbon composite material prepared in Comparative Example 4 was used as the electrode active material to prepare a battery with constant current charge and discharge cycle performance, as shown in FIG. Fig.14 As shown in the figure, after 35 charge and discharge cycles at a current density of 0.1A / g, the capacity decay is quite obvious, and the capacity of the battery is only 254mAh / g, which is 78.82% lower than that of Example 1, indicating that only the battery prepared by using ammonium chromate and dopamine hydrochloride to form a spherical complex and using it as a template to obtain chromium trisulfide-carbon composite microspheres through heat treatment and sulfurization has good cycle stability. The composite material prepared by simply coating with dopamine hydrochloride in Comparative Example 4 still has poor cycle stability.
[0098] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing chromium trisulfide-carbon composite microspheres, characterized in that: The steps include: S1. mixing the chromate solution and the dopamine hydrochloride solution dropwise for reaction, and post-treating to obtain a complex precursor of dopamine and chromate; S2. In an inert atmosphere, the complex precursor and the sulfur source are heat treated and sulfurized at 600 to 800°C, and post-treated to obtain chromium trisulfide-carbon composite microspheres; Wherein, the molar ratio of dopamine hydrochloride to chromate is (1-2):
1.
2. The preparation method according to claim 1, characterized in that: The molar concentration of chromate ions in the chromate solution is 0.01-0.5 mol / L.
3. The preparation method according to claim 1, characterized in that: The molar ratio of the sulfur source to the chromate is (5-10):
1.
4. The preparation method according to claim 1, characterized in that: The chromate is one or more of ammonium chromate, potassium chromate and sodium chromate.
5. The preparation method according to claim 1, characterized in that: The sulfur source is one or both of thiourea and thioacetamide.
6. The preparation method according to claim 1, characterized in that: The heat treatment and vulcanization time is 1 to 4 hours.
7. The preparation method according to claim 1, characterized in that: The temperature of the heat treatment and vulcanization is 650-700°C.
8. Chromium trisulfide-carbon composite microspheres prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the chromium trisulfide-carbon composite microspheres according to claim 8 in the preparation of supercapacitors, lithium ion batteries or sodium ion batteries.
10. A lithium ion battery, characterized in that: The negative electrode material in the lithium-ion battery contains the chromium trisulfide-carbon composite microspheres described in claim 8.